Proposed motorcycle towing device attached to the plus pickup trucks - Mohd Hanif Mohammad yusof (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is mainly about desing and development of an apparatus to carry the problematic motorcle. The problem faced by PLUS maintenance worker is been solved by designing this device. Usually, the worker will lift up the motocycle to the pickup truck using hand and it take more energy. The repeated works cause back pain and fatigue trus cause the worker reflused to o their work. The action cause loss in work. Relate to problem,